Maurice A novel - Forster, E. M. 1879-1970 (Arnold, 1971)
Set in pre-World War I England, this film concerns the coming of age of two young men who meet at Cambridge and fall in love. Maurice and Clive strugggle with the desires of their hearts and the rigid constraints of society.